Where Have I Heard That Song Before? - Arbuckle, Donald S. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article is a personal response to the theme of this issue — a theme which is notentirely "new". The writer remains unconvinced that counsellors should become more like teachers, but rather suggests that they continue to relate to their clients in a very special way that helps to release their potential not only to do their own thing but also to make someone elses' thing their thing. Counsellors are urged to discover themselves first, then turn their attention to ways in which they might effectively help others.